PRODUKSI DEKSTRIN UBIKAYU MELALUI METODE GELATINISASI SEBAGIAN MENGGUNAKAN ROTARY DRUM - Surfiana Surfiana; Siti Nurdjanah; Nurbani Kalsum; Liana Verdini (Jurnal Teknologi & Industri Hasil Pertanian, 2013)
This research was aimed to obtain the optimum  condition and characteristics of  dextrin processed  from tapioca(cassava starch) by using partial gelatinization using  drum dryer. This experiment was arranged in randomized compelete block design with three factors and three replications. The first factor was (V) cassava varieties, which consisted of Cassesart/UJ-5 (V1) and Thailand/UJ-3  (V2). The second factor (K) was the concentration which consisted of three levels : 30 % (K1), 35 % (K2), and 40 % (K3). The third factor (T) was the temperature of the partial gelatinization which consisted of three temperature levels that were 80o C (T1), 90oC(T2), and 100oC(T3). Characterization was conducted on dextrin  processed from tapioca  included chemical and physical characteristics (water absorption, and water solubility). The results showed that the varieties of cassava, concentration, and temperature have significant effect on dextrin saccharide composition, solubility in water, and swelling power.  Thailand variety, 35 % concentration, and processing temperature of    90o C  produced dextrin with better functional characteristics , which were  24 % of dextrin composition, 77,15 % of solubility, and 6,89 %  of swelling power. Key words : Cassava, dextrin, parsial gelatinazation, rotary drum.